Peran Pembina Remaja untuk Perkembangan Perilaku Remaja di Jemaat GMIM Golgota - Spenerhard Makahinsade (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2023)
Abstract: This paper is a theological analysis for holding a youth worship meeting which is held once every two weeks face to face. So the authors want to conduct research scientifically by studying the